The influence of auditory hypersensitivity on individuals diagnosed with Autism Spectrum Disorder (Research, Society and Development, 2024)
Objective: To expose the impacts of auditory sensitivity in patients diagnosed with Autism Spectrum Disorder (ASD) on their social interaction skills, highlighting the limitations imposed and repetitive behavior patterns, in addition to their correlations with changes in auditory perception. Method: This is an Integrative Literature Review that began searching in February and March 2024 and after a rigorous selection of studies, 22 scientific articles were selected to construct the work. Discussion and results: Autism Spectrum Disorder (ASD), a condition with multifactorial etiology involving genetic components and environmental influences, has experienced an increase in its frequency of diagnosis in contemporary society, particularly in children. It is widely recognized that one of the striking characteristics of individuals with ASD is the manifestation of disproportionate behaviors in response to sound stimuli. This phenomenon often manifests itself in the form of hyperacusis, misophonia and phonophobia, among other characteristics. The auditory hypersensitivity observed in patients with ASD lacks a definitive pathophysiological explanation, although several theories have been proposed to elucidate this phenomenon.